Voluptuous Devices; Exuberent Materiality toward Energy Austerity. (June 2014) - Weston, Mark; Greenberg, Dan
This paper proposes strategies for performance-based architectural devices characterized by a distinct material exuberance. The engineered predictability of typical building systems is challenged in favor of biological performance modes ruled by scales, sweat, and curves rather than shipping, manufacturing, and commerce. In the realm of traditional ceramic hand- making and manufacture, computation and CNC fabrication are two powerful tools which position the craftsman at the helm of a hybrid endeavor for smart materials.